Education and Human Rights: “Education As Everybody’s Right” - Angulo Ureña, Julio (2019)
Human beings are not always fully aware of their rights and what this implies to be able to enjoy them. That is why the need to research on the population’s knowledge of education as a right for all arose. Specifically, the research was carried out in the community of the southern border area, near the National University Brunca Region Campus, Coto, Costa Rica. Rights are a guarantee that all human beings have; the problem arises when the equality for which human beings fight so hard is not achieved. The right to education was analyzed as a social guarantee, covering aspects, such as situational analysis and socioeconomic problems of the region that could trigger problems in the future development of the country. Likewise, a methodological study was conducted through observation and questionnaires to a sample of the population of the border zone. Questions were analyzed, such as the current academic level of this population, approaches in the careers the National University offers, and the conditions of accessibility to education as a right. This meant and demonstrated the lack of knowledge of the inhabitants on the subject of public higher education as a right for all. In conclusion, the primary interest at all times was to know the access to information that this population has about education as a right and the opportunities that the National University is offering.